THE IMPACT OF FIRM SIZE AND PROFITABILITY (ROA) IN INDONESIA REAL ESTATE SECTOR COMPANIES (IDX) - Franco Benony Limba; Agnes Soukotta; Jabida Latuamury; Ratih Kusumastuti (Jurnal Ekonomi, 2023)
The purpose of this study was to determine the effect of firm size and profitability (ROA) on firm value. The sampling technique used purposive sampling method. Purposive sampling is a sample determination method based on certain criteria. The form of this research is associative research. Data analysis techniques were performed using descriptive statistical analysis, classical assumption test, multiple linear regression analysis, multiple correlation coefficient test, coefficient of determination, model feasibility test and t test. After processing and testing the data, it shows that the variable company size (Firm Size) has no effect on firm value (Firm Value), and profitability (ROA) has an influence in a positive direction on firm value (Firm Value).